Competitive antagonism of housefly γ-aminobutyric acid receptors by iminopyridazine butanoic acids - Rahman, MM; Ozoe, F; Ozoe, Y (Bangladesh Journal of Scientific and Industrial Research, 2021)
The competitive antagonistic activities of a series of gabazine (3) based 3-substituted iminopyridazine butanoic acid analogs [4-(3-aryl/heteroaryl-1,6-dihydro- 6-iminopyridazin-1-yl) butanoic acid hydrochlorides] 4a-4k (Figure 1) were examined at housefly (Musca domestica) GABA receptors expressed in Xenopus oocytes using two-electrode voltage-clamp (TEVC) technique. The 4-biphenylyl analog 4e exhibited the highest inhibition (approximately 68%) of GABA-induced currents at 100 μM with an IC50 value of 40.81 ± 3.89 μM. The 2-naphthyl analog 4h was the second most active compound with approximately 48% inhibition. The 4-biphenylyl analog 4e demonstrated competitive antagonism of housefly GABA receptors. Ligand docking studies into the binding site of housefly GABA receptor homology model predicted that the aromatic 3-substituents are tolerable in the pyridazine ring. The results presented in this paper about GABA receptor competitive antagonists may helpful for design and development of GABA receptor related insecticides. Bangladesh J. Sci. Ind. Res.56(1), 9-16, 2021